Safeguarding Places of Worship during the Prophetic Era: Assessment of Early Islamic Covenants and Their Impacts on Early Muslim Polities - Mehfooz, Musferah (Religions, 2022)
Treaties and covenants have been the most important instruments of international relations in both ancient and modem times, playing a significant role in the promotion of religious freedom, peaceful coexistence, and interfaith harmony. The rapid spread and broad appeal of early Islam brought matters of international relations and cosmopolitan state governance to a cadre of Muslim leaders whose main political experience had been with parochial Arabian tribalism. The foremost issue was the position, rights, and responsibilities of non-Muslim religious communities within the Arab-Islamic empire. Consequently, numerous covenants and treaties were devised with subjects and with foreign states during the expansion of the Muslim world. This study examines the protection of non-Muslim places of worship under the rule of the Prophet Muḥammad ﷺ and his successors, including future caliphs and generals. It explores the practical application of the covenants by the successors of the Prophet Muḥammad ﷺ during early Islamic history, exploring the extent to which these covenants and treaties were effective in maintaining peaceful co-existence in a multi-faith society. In sum, for the sake of concision, only specific segments of the covenants and treaties are examined, which were devised with the non-Muslims for the protection of their worship places during the early Muslim Conquests.